2004
DOI: 10.1111/j.1399-3054.2004.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

FtsH proteases in chloroplasts and cyanobacteria

Abstract: FtsH is a membrane‐bound ATP‐dependent metalloprotease complex found in prokaryotes and organelles of eukaryotic cells. It consists of one or two trans‐membrane helices at its amino‐terminus, a highly conserved ATPase domain, which relates it to the AAA protein family, and a zinc‐binding domain towards its carboxy‐terminus that serves as the proteolytic site. Most bacteria contain a single FtsH gene, but the cyanobacterium Synechocystis has four. The Arabidopsis thaliana genome contains 12 genes encoding FtsH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 23 publications
2
38
0
2
Order By: Relevance
“…The Arabidopsis thaliana chloroplast also contains a number of FtsH homologues, all nucleus-encoded (16). Of these, FtsH2 (VAR2) has been shown to be involved in D1 degradation (17), but other FtsH members are also likely to participate (18,19).…”
mentioning
confidence: 99%
“…The Arabidopsis thaliana chloroplast also contains a number of FtsH homologues, all nucleus-encoded (16). Of these, FtsH2 (VAR2) has been shown to be involved in D1 degradation (17), but other FtsH members are also likely to participate (18,19).…”
mentioning
confidence: 99%
“…Taken together, these results suggested that the chloroplast FtsH complex is a hetero-oligomer composed of two types of subunits, each encoded by duplicated genes. Whereas subunits within a type are redundant, the presence of subunits from both types is essential for accumulation of the complex (Adam et al 2005(Adam et al , 2006Zaltsman et al 2005b). Moreover, previous quantification of the different isomers (Sinvany-Villalobo et al 2004) now suggests that the FtsH hexamer is composed of two subunits of 'type A'-FtsH1 and/or FtsH5, and four subunits of 'type B'-FtsH2 and/or FtsH8 (Zaltsman et al 2005b;Adam et al 2006).…”
Section: Ftsh Proteasementioning
confidence: 94%
“…The FtsH gene family in Arabidopsis contains twelve members (for recent reviews, see Adam et al 2005Adam et al , 2006Sakamoto 2006). Products of three of these (FtsH3, FtsH4, and FtsH10) are targeted to the mitochondria whereas the other nine (FtsH1, FtsH2, FtsH5-FtsH9, FtsH11, and FtsH12) are targeted to the chloroplasts, as revealed by transient-expression assays with GFP fusions (Sakamoto et al 2003).…”
Section: Ftsh Proteasementioning
confidence: 98%
See 1 more Smart Citation
“…A multiplicação dos genes das proteases FtsH se correlaciona fortemente com a evolução da fotossíntese, muito provalmente devido ao aumento do estresse oxidativo e a consequente maior quantidade de danos as proteínas (ADAM et al, 2005). As bactérias contem apenas uma cópia do gene FtsH, ao passo que cianobactérias possuem quatro destes genes (MANN et al, 2000) e as plantas superiores possuem ainda mais cópias, como exemplo A. thaliana possui uma família gênica com 17 membros, com 12 deles codificando para isoformas ativas (GARCIA-LORENZO et al 2006).…”
Section: -Inferência Filogenética E Classificação Dos Homólogos Das Punclassified